Antibiotic Inhibition of the Septation Stage in Sporulation of Bacillus megaterium - Hitchins, Anthony D. (1969)
The inhibition of sporulation septation (stage II) in Bacillus megaterium was shown with penicillin, d-cycloserine, bacitracin, vancomycin, novobiocin, chloromycetin, streptomycin, mitomycin C, and nalidixic acid.